Evaluating the success of distance learning among students of Marka Education Directorate in Jordan from parents’ perspective and its relationship to some variables - Khader, Arwa Mustafa (Journal of Educational and Psychological Sciences, 2022)
The study aims to investigate the evaluation of parents in Marka Directorate of distance learning for their children from their perspective, and to identify if there were differences due to the variables: school type and children’s educational stage. To achieve the purpose of this study, the researcher designed a questionnaire consisting of (24) items covering three areas. The study sample included (1360) parents, and the results indicated that parents’ evaluation of distance learning came to a medium degree, and the actions taken by families regarding distance learning and their participation received the highest response with a high degree, and the field of presence of skills of using computer applications came in the second with a medium degree, and the level of families’ financial capability came in the third with a medium degree. The results showed the presence of differences depending on the type of school and the superiority of private schools over public, UNRWA schools and military schools, and the presence of statistically significant differences according to the variable of the educational stage in favor of the students’ stage from the seventh to the tenth grade.
Keywords: evaluation of distance learning; distance learning; distance learning success